The Effectiveness of Group Counseling Using a Humanistic Existential Approach in Reducing FOMO Learning in the New Normal Era - Yadi, Heri Febri; Firman, Firman; Netrawati, Netrawati (Widyagogik, 2023)
Indonesia, such as the increasing spending of money by the younger generation and the rise of social media applications, makes the younger generation always want to satisfy their emotional needs, but they don't have enough money so that it becomes social pressure for the younger generation. Anxiety about being left behind makes it difficult for this generation to say no, and this phenomenon is one of the factors why there is Fomo syndrome. This study contains problem solving from FOMO Learning in the New Normal Era, with Humanistic Existence through Group Counseling to increase student learning responsibility, assistance to individuals in group situations that are prevention and healing, and directed at providing convenience in class development and growth. This research is research designed using the library method. The results are in the form of Humanistic Existential counseling emphasizing core human conditions. Normal personality development is based on the uniqueness of each individual.